Role of The School Administration in Applying the Quality Standards in Teaching Among Islamic Education Teachers Perspectives in The Directorate of Education in The Zarqa Region - Yassen, Omar AbdelAziz Mosa (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the role of the school administration in applying the quality standards in teaching among Islamic education teachers Perspectives in the Directorate of Education in the Zarqa Region study sample consisted of (72) male teachers and (88) female teachers. To achieve the objectives of the study, The descriptive approach was used a questionnaire was used as a tool for data collection; The result showed that the level of the role of the school administration in applying the quality standards in teaching among Islamic education teachers was High with (3.71) score the stander of planning gets the highest score with (4.85) degree then the stander of implementation the lesson was also high with (3.83) score finally the stander of the evaluation was moderate with (3.56) score The finding also showed there are no statistically significant differences between the level of Islamic Education teachers sex (male and female) in addition there were statistically significant differences refers to years of experience in favor of the five and less. - In light of these results, there are a set of recommendations and suggestions to maintain quality standards in teaching and to improve evaluation quality in Zarqa School and in the whole of the kingdom of Jordan and Arab countries.